2011
DOI: 10.1371/journal.pone.0014797
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes CAMP Factor and Host Acid Sphingomyelinase Contribute to Bacterial Virulence: Potential Targets for Inflammatory Acne Treatment

Abstract: BackgroundIn the progression of acne vulgaris, the disruption of follicular epithelia by an over-growth of Propionibacterium acnes (P. acnes) permits the bacteria to spread and become in contact with various skin and immune cells.Methodology/Principal FindingsWe have demonstrated in the present study that the Christie, Atkins, Munch-Peterson (CAMP) factor of P. acnes is a secretory protein with co-hemolytic activity with sphingomyelinase that can confer cytotoxicity to HaCaT keratinocytes and RAW264.7 macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 63 publications
2
89
1
1
Order By: Relevance
“…There have been many previously published vaccine studies on ICR mice [29][32]. ICR mice are outbred mice with genetic functional diversity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many previously published vaccine studies on ICR mice [29][32]. ICR mice are outbred mice with genetic functional diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with P. acnes CAMP factor 2 (50842175), found in all phylotypes we examined, showed promise in animal models (Liu et al, 2011;Nakatsuji et al, 2011). Some of the cell surface proteins expressed only in acne or neutral strains such as the cell wall hydrolase (50843410), adhesion (50843565), or others may also be interesting to evaluate as vaccine candidates.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Indeed, previous studies have shown an association between the putative CAMP factor and virulence (44,45). Rühlmann et al (46) have shown that the CAMP factor of GBS, a 25-kDa protein named protein B, binds to immunoglobulins in a way similar to that of protein A of S. aureus.…”
Section: Discussionmentioning
confidence: 99%